Analisis Pengaruh Pelayanan dan Fasilitas terhadap Kepuasan Penumpang di Bandar Udara Tjilik Riwut Palangkaraya - Bella Nova Rosefira (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Airport services and facilities greatly affect the level of passenger satisfaction, with very adequate facilities,Tjilik Riwut Airport service users will feel satisfied from the company's performance.The level of quality of service and facilities cannot be measured from the airline's point of view but must be seen from the point of view of passenger satisfaction.Evaluate the airline's current position with other competitors. The formulation of the problem from this research Is there an effect of service on passenger satisfaction at Tjilik Riwut Airport Palangkaraya,Is there an effect of facilities on passenger satisfaction at Tjilik Riwut Palangkaraya Airport,Is there an effect of facilities and services on passenger satisfaction at Tjilik Riwut Airport Palangkaraya.Research Objectives This study aims to determine whether there is an effect of service on passenger satisfaction at Tjilik Riwut Airport,Palangkaraya,then whether there is an effect of facilities on passenger satisfaction at Tjilik Riwut Airport,Palangkaraya,and whether there is an effect of service facilities on passenger satisfaction at Tjilik Riwut Airport,Palangkaraya. This research uses quantitative methods.The population in this study were all passengers or service users of Palangkaraya Tjilik Riwut Airport, totaling 142,379 passengers.The number of samples is 100 respondents.Service variable (X1) has a positive effect on passenger satisfaction (Y).The coefficient of the facility variable is 0.142,for the facility T count (X2) is 3.411>1.984 so it can be concluded that the facility variable (X2) has a positive effect on passenger satisfaction (Y). Keywords: Service, facilities, Passenger Satisfaction